IMPLEMENTASI LAYANAN KETATAUSAHAAN - Nabila; Ajat rukajat; Chairil Fajar Hadiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Administrative services play an important role in supporting the smooth implementation of education through effective, efficient, and well-organized administrative management. This study aims to describe and analyze the implementation of administrative services at SMPN 2 Kedungwaringin. The study employed a qualitative approach using a descriptive method. Data were collected through interviews, documentation, and the examination of school administrative records. The data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of administrative services at SMPN 2 Kedungwaringin has been carried out effectively and has supported the educational process. The implementation is reflected in three main aspects: the provision of school administrative services, the daily administrative activities of the administration office, and the role of the principal in managing and supervising administrative operations. School administrative services are conducted systematically through correspondence management, document filing, data storage, and regular updating of school records. Daily administrative activities include the management of incoming and outgoing correspondence, student and staff data administration, preparation of administrative reports, and the provision of administrative support for all school stakeholders. In addition, the principal plays an active role in ensuring the effectiveness of administrative services through monitoring, guidance, supervision, and periodic evaluation of administrative staff performance. Therefore, the implementation of administrative services at SMPN 2 Kedungwaringin can be considered orderly, effective, and supportive of both service quality improvement and the smooth operation of educational activities within the school.